PENINGKATAN LARI CEPAT DENGAN PERMAINAN SPEED COLOUR PADA SISWA KELAS V MADRASAH IBTIDAIYAH AL HUDA MANGLI KECAMATAN RANDUDONGKAL KABUPATEN PEMALANG TAHUN PELAJARAN 2012 / 2013 (Department of Physical Education, Sport, Health and Recreation, 2013)
This study was conducted at Al Huda Islamic Elementary School District Mangli Randudongkal Pemalang inclass V odd semester. Research object in this study is that there are 39 class V students. The data analysis usingteacher assessment activity sheets that were used to obtain the skills of teachers in providing learning,assessment of student activity sheets that were used to obtain the skills students covering aspects of psychomotor,affective and cognitive aspects, practice tests and questionnaires were used to evaluate the response students tothe game of color-tailed (Bonakor). The results in the students' ability to perform a series of attitudes start,while running, he entered the finish line increased from 76% to limit completed by the end of the first cycle andincreased to 95% or to reach the limit due at the end of the second cycle.